Tìm x:
a, 45451: x = 151
b, x x 35 = 25 x 49
Bài3:Tìm x:
a) 71 – (33 + x) = 26 b) (x + 73) – 26 = 76 c) 45 – (x + 9) = 6 d) 89 – (73 – x) = 20 e) 4(x + 41) = 400 f) 11(x – 9) = 77 | g) (x + 7) – 25 = 13 h) 198 – (x + 4) = 120 i) 5(x – 9) = 350 j) 2x – 49 = 5.32 k) 25 + 3(x – 8) = 106 l) 32(x + 4) – 52 = 5.22 | m) 200 – (2x + 6) = 43 n) 2(x- 51) = 2.23 + 20 o) 450 : (x – 19) = 50 p) 4(x – 3) = 72 – 110 q) 156 – (x+ 61) = 82 r) (x-35) -120 = 0 |
a: Ta có: \(71-\left(x+33\right)=26\)
\(\Leftrightarrow x+33=45\)
hay x=12
b: Ta có: \(\left(x+73\right)-26=76\)
\(\Leftrightarrow x+73=102\)
hay x=29
c: Ta có: \(45-\left(x+9\right)=6\)
\(\Leftrightarrow x+9=39\)
hay x=30
a) 71 - ( 33 + x ) = 26
(33 + x ) = 71 -26
33 + x = 45
x = 45 - 33 = 12
b) ( x + 73 ) - 26 = 76
( x + 73 ) = 102
x = 102 - 73 = 29
c) 45 - ( x + 9 ) = 6
( x + 9 ) = 45 - 6 = 39
x = 39 - 9 = 30
d) 89 - ( 73 - x ) = 20
73 - x = 89 - 20
73 - x = 69
x = 73 - 69 = 4
e) 4(x+41) = 400
x + 41 = 400 : 4 = 100
x = 100 - 41 = 59
f) 11(x-9 ) = 77
x - 9 = 77 : 11 = 7
x = 7 + 9 = 16
g) x + 7 = 25 + 13 = 38
x = 38 - 7 = 31
h) x + 4 = 198 - 120 = 78
x = 78 - 4 = 74
i) x - 9 = 350 : 5 = 70
x = 70 + 9 = 79
j) 2x - 49 = 5 . 9 = 45
2x = 45 + 49 = 94
x = 94 : 2 = 47
k) 25 + 3( x - 8 ) = 106
3(x-8 ) = 106 - 25 = 81
x - 8 = 81 : 3 = 27
x = 27 +8= 35
l) 9( x + 4 ) - 25 = 20
9( x + 4 ) = 20 + 25 = 45
x + 4 =45 : 9 = 5
x = 5 - 4 = 1
m) 200 - ( 2x + 6 ) = 64
2x + 6 = 200 - 64 = 136
2x = 136 - 6 = 130
x = 130 : 2 = 65
n) 2(x-51) = 16 + 20 = 36
x - 51 = 36 : 2 = 13
x = 13 + 51 = 64
o) 450 : ( x - 19 ) = 50
x - 19 = 450 : 50 = 9
x = 19 + 9 = 28
p)4(x-3) = 49 - 1 = 48
x - 3 = 48 : 4 = 12
x + 15
q) 156 - ( x+61 ) = 82
x + 61 = 156 - 82 = 74
x = 74 - 61 = 13
r) ( x - 35 ) - 120 = 0
x - 35 = 120
x = 120 + 35 = 155
Tìm x biết:
a ) 4 9 + x = - 5 3 b ) 2 5 + 3 5 : x = 1 7 10 c ) 40 % x - 3 5 x = 2 35 d ) 2 x + 1 2 = 49
d) ( 2 x + 1 ) 2 = 49
2x + 1 = 7 hoặc 2x + 1 = -7
2x = 6 hoặc 2x = -8
x = 3 hoặc x = -4
Tìm x:
a. 4x2 - 20x + 25 = 0
b. (x - 5)(x + 5) - (x - 3)2 = 2(x - 7)
a. `4x^2-20x+25=0`
`<=>(2x)^2-2.2x.5 +5^2=0`
`<=>(2x-5)^2=0`
`<=>2x-5=0`
`<=>x=5/2`
b. `(x-5)(x+5)-(x-3)^2=2(x-7)`
`<=>x^2-25-x^2+6x-9=2x-14`
`<=>6x-34=2x-14`
`<=>4x=20`
`<=>x=5`
\(a,4x^2-20x+25=0\Leftrightarrow\left(2x\right)^2-2.2x.5+5^2=0\)
\(\Leftrightarrow\left(2x-5\right)^2=0\Leftrightarrow x=\dfrac{5}{2}\)
b, \(\left(x-5\right)\left(x+5\right)-\left(x-3\right)^2=2\left(x-7\right)\)
\(\Leftrightarrow x^2-25-x^2+6x-9=2x-14\Leftrightarrow4x=20\Leftrightarrow x=5\)
a) Có: (2x)2 - 2.2.5.x + 52 = 0
⇒ (2x - 5)2 = 0 ⇒ 2x - 5 = 0
⇒ 2x = 5 ⇒ x = \(\dfrac{5}{2}\)
b) Có: x2 - 25 - x2 + 6x - 9 = 2x - 14
⇒ 6x - 36 = 2x - 14
⇒ 4x = 22
⇒ x = \(\dfrac{11}{2}\)
Tìm x:
a) 5x(x-2)+(2-x)=0
b) x(2x-5)-10x+25=0
c) \(\dfrac{25}{16}\)-4x2+4x-1=0
d)x4+2x2-8=0
a) \(\text{5x(x-2)+(2-x)=0}\)
\(\Rightarrow5x\left(x-2\right)-\left(x-2\right)=0\\ \Rightarrow\left(x-2\right)\left(5x-1\right)=0\\ \Rightarrow\left[{}\begin{matrix}x-2=0\\5x-1=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=2\\x=\dfrac{1}{5}\end{matrix}\right.\)
b) \(\text{x(2x-5)-10x+25=0}\)
\(\Rightarrow x\left(2x-5\right)-5\left(2x-5\right)=0\\ \Rightarrow\left(x-5\right)\left(2x-5\right)=0\\ \Rightarrow\left[{}\begin{matrix}x-5=0\\2x-5=0\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}x=5\\x=2,5\end{matrix}\right.\)
c) \(\dfrac{25}{16}-4x^2+4x-1=0\)
\(\Rightarrow\dfrac{9}{16}-4x^2+4x=0\)
\(\Rightarrow-4x^2+4x+\dfrac{9}{16}=0\)
\(\Rightarrow-4x^2-\dfrac{1}{2}x+\dfrac{9}{2}x+\dfrac{9}{16}=0\)
\(\Rightarrow\left(-4x^2-\dfrac{1}{2}x\right)+\left(\dfrac{9}{2}x+\dfrac{9}{16}\right)=0\)
\(\Rightarrow-\dfrac{1}{2}x\left(8x+1\right)+\dfrac{9}{16}\left(8x+1\right)=0\)
\(\Rightarrow\left(-\dfrac{1}{2}x+\dfrac{9}{16}\right)\left(8x+1\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}-\dfrac{1}{2}x+\dfrac{9}{16}=0\\8x+1=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=\dfrac{9}{8}\\x=\dfrac{-1}{8}\end{matrix}\right.\)
a) \(5x\left(x-2\right)+\left(2-x\right)=0\)
\(\Rightarrow5x\left(x-2\right)-\left(x-2\right)=0\)
\(\Rightarrow\left(x-2\right)\left(5x-1\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x-2=0\\5x-1=0\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}x=2\\x=\dfrac{1}{5}\end{matrix}\right.\)
b) \(x\left(2x-5\right)-10x+25=0\)
\(\Rightarrow x\left(2x-5\right)-5\left(2x-5\right)=0\)
\(\Rightarrow\left(x-5\right)\left(2x-5\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x-5=0\\2x-5=0\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}x=5\\x=\dfrac{5}{2}\end{matrix}\right.\)
c) \(\dfrac{25}{16}-4x^2+4x-1=0\)
\(\Rightarrow-4x^2+4x+\dfrac{9}{16}=0\)
\(\Rightarrow\left(x-\dfrac{9}{8}\right)\left(x+\dfrac{1}{8}\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x-\dfrac{9}{8}=0\\x+\dfrac{1}{8}=0\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}x=\dfrac{9}{8}\\x=-\dfrac{1}{8}\end{matrix}\right.\)
d) \(x^4+2x^2-8=0\)
\(\Rightarrow\left(x^4+2x^2+1\right)-9=0\)
\(\Rightarrow\left(x^2+1\right)^2-3^2=0\)
\(\Rightarrow\left(x^2+1-3\right)\left(x^2+1+3\right)=0\)
\(\Rightarrow\left(x^2-2\right)\left(x^2+4\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x^2-2=0\\x^2+4=0\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}x^2=2\\x^2=-4\end{matrix}\right.\) \(\Rightarrow x^2=2\) \(\Rightarrow x=\pm\sqrt{2}\)
Tìm chữ số tận cùng: 11 x 13 x 15 x 17 + 23 x 25 x 27 x 29 + 31 x 33 x 35 x 37 + 45 x 47 x 49 x 51
11 x 13 x 15 x 17 + 23 x 25 x 27 x 29 + 31 x 33 x 35 x 37 + 45 x 47 x 49 x 51
=7096860
#Hok tốt!#
1,Tính nhanh
a, 568 + 568 x 135 - 568 x 36
b, 17 x 49 + 49 x 37 + 54 x 26 + 54 x 25
c, 14 x 35 x 5 + 10 x 25 x 7 + 20 x 70
a, 568 + 568 x 135 - 568 x 36
= 568 x ( 1 + 135 - 36)
= 568 x 100
56 800
b, 17 x 49 + 49 x 37 + 54 x 26 + 54 x 25
= 49 x ( 17 + 37) + 54 x ( 26 + 25 )
= 49 x 54 + 54 x 51
= 54 x ( 49 + 51)
= 54 x 100
= 5 400
c, 14 x 35 x 5 + 10 x 25 x 7 + 20 x 70
= ( 2 x 35) x ( 7 x 5) + ( 10 x 7) x 25 + 20 x 70
= 70 x 35 + 70 x 25 + 20 x 70
= 70 x ( 35 + 25 + 20)
= 70 x 80
= 5 600
a) 568 + 568 x 135 - 568 x 36
= 568 x ( 1+1+135-1-36 )
=568 x 100
=5680
b) 17 x 49 + 49 x 37 + 54 x 26 + 54 x 25
= 49 x ( 17 + 37 ) + 54 x ( 26 + 25 )
= 49 x 54 + 54 x 51
= 54 x ( 49 + 51 )
= 54 x 100
= 5400
c) 14 x 35 x 5 + 10 x 25 x 7 + 20 x 70
= 70 x 35 + 10 x 25 x 7+ 20 x 70
= 70 x 35 + 250 x 7 + 20 x 70
= 70 x 35 + 70 x 25 + 20 x 70
= 70 x (35+25+20)
= 70 x 80
= 5600
Tìm X:
a, 25 + 3 ( x-8 ) = 106
b, 3 mũ 2 ( x+4 ) - 5 mũ 2 = 5.2 mũ 2
Tìm X:
a, 25 + 3 ( x-8 ) = 106
b, 3 mũ 2 ( x+4 ) - 5 mũ 2 = 5.5 mũ 2
a. 25 + 3(x-8) = 106
3(x-8) = 106 - 25 = 81
x -8 = 81 : 3 = 27
x = 27 +8 = 35
b. 32(x +4) - 52 = 5.52
9(x+4) - 25 = 5.25 = 125
9(x+4) = 125 + 25 = 150(Đề sai)
Tìm X:
a, 25 + 3 ( x-8 ) = 106
b, 3 mũ 2 ( x+4 ) - 5 mũ 2 = 5.2 mũ 2
3.(x-8) = 106-25
3.(x-8) = 81
x-8 = 81:3
x-8 = 27
x=35
\(a,25+3\left(x-8\right)=106\\ 3\left(x-8\right)=81\\ x-8=27\\ x=35\)
32 . (x + 4 ) - 52 = 5 . 22
9 . ( x + 4 ) - 25 = 20
9 . ( x + 4 ) = 20 + 25
9 . ( x + 4 ) = 45
( x + 4 ) = 45 : 9
x + 4 = 5
x = 5 - 4
x = 1